Pengaruh Sifat Machiavellian dan Perkembangan Moral terhadap Dysfunctional Behavior dengan Gender sebagai Variabel Moderasi. - Widyawati, Feny; Sukhemi, Sukhemi (AKMENIKA, 2017)
This study aims to find out about the Machiavellian Influence of Personality and Moral Development of the Dysfunctional Behavior by Gender as a moderating variable. The sample used was a student S1 Accounting End Level PGRI University of Yogyakarta. Data obtained by purposive sampling method. The data collection is done by using a questionnaire. A total of 90 questionnaires distributed and 81 questionnaires which can be recycled. The research hypotheses were tested using multiple regression analysis and test MRA (Moderated Regression Analysis) with SPSS.The results showed that the positive effect on the Machiavellian nature of dysfunctional behavior, and negatively affect the moral development of dysfunctional behavior. As for the result of the interaction between dysfunctional behavior and gender showed that gender can not moderate influence Machiavellian nature and moral development of the dysfunctional behavior.